Factors Associated with Self-Reported Health (SRH) among Nepalese Older Men (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Background: Self-reported health (SRH) is a subjective measurement tool of overall health status. It integrates with the biological, social, mental, and functional aspects of individuals. The aim of this article is to assess the SRH and its correlates among community-living older men from Nepal.Methods: This study uses the secondary data collected by the Central Department of Population Studies at Tribhuvan University (TU). This study includes community-dwelling male elderly aged 60+ in the Pharping area of Kathmandu. For this study, there were 657 valid responses. A simple and direct question was used “In general, how do you rate your general health?” Its answer was recorded on the 5-point Likert scale “Very Good to Very Bad”.Results: The mean age of the participants was 69.51 years. The majority of respondents (75.9%) live with family members. People who reported poor SRH were 17.0%. Many of them have physical health problems (73.2%) and mental health problems (57.2%). Mental health problems, age of respondents, physical health problems, satisfaction with current living arrangements, walking efficiency, adequate income sources, Insecurity feelings, Income sufficient to fulfill the basic needs, and current working were correlated with SRH. However, linear regression shows that satisfaction with walking efficiency, physical health, and working situation, were significant predictors of SRH.Conclusion: This analysis suggests that working, walking ability, physical health problems, and financial adequacy are significantly associated with self-rated health. Identifying these variables through self-rated status can support the planning of actions aimed at improving the health of the community living older adult men in Nepal.